Severe Outcomes Associated With SARS-CoV-2 Infection in Children: A Systematic Review and Meta-Analysis - Madeleine W. Sumner; Alicia Kanngiesser; Kosar Lotfali-Khani; Nidhi Lodha; Diane Lorenzetti; Anna L. Funk; Stephen B. Freedman (Frontiers Media S.A., 2022)
ObjectiveTo estimate the proportion of SARS-CoV-2 infected children experiencing hospitalization, intensive care unit (ICU) admission, severe outcomes, and death.Data SourcesPubMed, Embase, and MedRxiv were searched for studies published between December 1, 2019 and May 28, 2021. References of relevant systematic reviews were also screened.Study SelectionWe included cohort or cross-sectional studies reporting on at least one outcome measure (i.e., hospitalization, ICU admission, severe outcomes, death) for ≥100 children ≤21 years old within 28 days of SARS-CoV-2 positivity; no language restrictions were applied.Data Extraction and SynthesisTwo independent reviewers performed data extraction and risk of bias assessment. Estimates were pooled using random effects models. We adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines.Main Outcomes and MeasuresPercentage of SARS-CoV-2 positive children experiencing hospitalization, ICU admission, severe outcome, and death.Results118 studies representing 3,324,851 SARS-CoV-2 infected children from 68 countries were included. Community-based studies (N = 48) reported that 3.3% (95%CI: 2.7-4.0%) of children were hospitalized, 0.3% (95%CI: 0.2-0.6%) were admitted to the ICU, 0.1% (95%CI: 0.0-2.2%) experienced a "severe" outcome and 0.02% (95%CI: 0.001-0.05%) died. Hospital-based screening studies (N = 39) reported that 23.9% (95%CI: 19.0-29.2%) of children were hospitalized, 2.9% (95%CI: 2.1-3.8%) were admitted to the ICU, 1.3% (95%CI: 0.5-2.3%) experienced a severe outcome, and 0.2% (95%CI: 0.02-0.5%) died. Studies of hospitalized children (N = 31) reported that 10.1% (95%CI: 6.1-14.9%) of children required ICU admission, 4.2% (95%CI: 0.0-13.8%) had a severe outcome and 1.1% (95%CI: 0.2-2.3%) died. Low risk of bias studies, those from high-income countries, and those reporting outcomes later in the pandemic presented lower estimates. However, studies reporting outcomes after May 31, 2020, compared to earlier publications, had higher proportions of hospitalized patients requiring ICU admission and experiencing severe outcomes.Conclusion and RelevanceAmong children tested positive for SARS-CoV-2, 3.3% were hospitalized, with rates being higher early in the pandemic. Severe outcomes, ICU admission and death were uncommon, however estimates vary by study population, pandemic timing, study risk of bias, and economic status of the country.Systematic Review RegistrationPROSPERO, identifier [CRD42021260164].